Risk of autoimmune diseases in recurrent aphthous ulcer patients: A nationwide population study. (30th December 2020) - Lee, Young Chan; Jeong, Su Jin; Eun, Young‐Gyu; Song, Ran; Oh, In‐Hwan
Abstract: Objective: To estimate the risk of developing autoimmune disease in patients diagnosed having recurrent aphthous stomatitis (RAS) through a nationwide population‐based cohort study. Methods: This study included two group of patients who had three or more episodes with aphthae diagnosed from their physician (RAS group) and a similar matched group of patients without aphthae (control group). Both groups were collected within the period of 2005–2007 from the Korean National Health Insurances claims database. Non‐RAS cohort was matched after frequency matching. The final enrolled subjects were observed during a follow‐up period from 2008 to 2015 and those who received autoimmune diseases diagnoses during follow‐up were identified. The hazard ratio (HR) for developing autoimmune diseases was estimated. Results: A total of 4, 637 patients with RAS and 4, 637 controls were included. The risk of overall autoimmune diseases was significantly increased in the RAS group (adjusted HR [aHR)], 1.19). With regard to each disease entity, patients with RAS showed an increased risk of Behcet's disease (31.16), systemic lupus erythematous (SLE) (1.74), ankylosing spondylitis (AS) (1.47), gout (1.47), Hashimoto thyroiditis (1.42), Graves' disease (1.37), and rheumatoid arthritis (RA) (1.19). Conclusion: RAS‐like lesion may be an early sign of systemic autoimmune disease, as it was associated with an increased risk of Graves' disease, Hashimoto thyroiditis, SLE, AS, gout, RA, and Behcet's disease from real‐world data.